(untitled) (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
Ngeloang Capah tradition is a tradition that is carried out from generation to generation that reflects a community belief and its implementation coincides with the Purnama Kedasa month once a year. The purpose of this study is to reveal the basis of the Ngeloang Capah tradition along with the philosophical values contained therein. This study uses a qualitative approach with interview, observation and documentation methods conducted in Tamblang Village. The results of the study indicate that the Ngeloang Capah tradition is an important part of the lives of the Tamblang Village community, the sacredness of this tradition is because there are myths that develop in the community and strong beliefs of the Tamblang Village community. In its implementation, the banten capah is used as a medium which is manifested in the yajña ceremony. The essence of the Ngeloang Capah tradition can be seen from the value of harmony reflected in the Tri Hita Karana teachings, harmony between humans and God as a manifestation of spirituality, harmony between humans and others such as the establishment of togetherness and good communication between each other and harmony with the environment in the form of environmental preservation. Ethical values that refer to moral behavioral norms that are upheld by society in establishing social and religious life. The value of cultural preservation is also one of the things that can be done by the Tamblang Village community by continuing to carry out traditions sustainably.